Isolation and biochemical characterization of the mammalian reovirus type 3 cell-surface receptor. - Co, M S (1985)
A cell-surface receptor for the mammalian reovirus type 3 hemagglutinin was isolated by using antiidiotypic anti-receptor antibodies. The receptor is a glycoprotein with a molecular mass of 67,000 daltons and a pI of 5.9. Evidence that the isolated structure represents the reovirus receptor was obtained by electrophoretic immunoblot studies, which demonstrated that the 67,000-dalton glycoprotein is the only cell-surface structure recognized by both reovirus type 3 and the anti-receptor immunoglobulin. Comparison of the reovirus receptor on murine thymoma (R1.1) and rat neuroblastoma (B104) cells indicated that similar structures on the cell surface are recognized by the reovirus type 3 and the anti-receptor antibodies as previously suggested from cellular and binding studies. This receptor was found on mouse, rat, monkey, and human cells. Furthermore, diverse tissue types, including lymphoid and neuronal cells, express the receptor structure. The receptor structure is discussed in terms of its role in mediating viral tropism and as an essential cell-surface protein.